Lung Function Is Associated with Arterial Stiffness in Children - Ayer, Julian G. (Public Library of Science, 2011)
BACKGROUND: In older adults, an independent association exists between impaired lung function and cardiovascular disease. This interaction might be related to the effects of aging and/or smoking. In order to explore possible childhood antecedents to this association, we hypothesized that decreased lung function and vascular stiffness might be related, in early life. OBJECTIVE: To determine the relationship between lung function and carotid augmentation index (AIx), a measure of vascular stiffness, in 8-year old children. METHODS: Data on brachial blood pressure, lung function (FEV(1), FVC, FEV(1)/FVC, obtained by spirometry) and carotid AIx75 (AIx standardised to an arbitrary heart rate of 75 beats per minute, obtained by applanation tonometry) was available in 249 community-based 8-year old children. These healthy children had been subjects in a randomised controlled trial of two interventions (omega-3 fatty acid supplementation and house-dust mite avoidance) to prevent asthma. Smoking in pregnancy and childhood environmental tobacco smoke (ETS) exposure was prospectively collected by questionnaire. The association between lung function and carotid AIx75 was assessed in multivariate models that included sex, height, smoking status during pregnancy, ETS exposure and randomisation groups (house dust mite avoidance and dietary intervention) as covariates. RESULTS: In the fully adjusted models, Carotid AIx75 was independently associated with FEV1 (standardised β = −0.17,b = −6.72, partial R(2) = .02, p = 0.03), FVC (standardised β = −0.29, b = −9.31, partial R(2) = 0.04, p<0.001) and FEV1/FVC (standardised β = .13, b = 18.4, partial R(2) = 0.02, p = 0.04). CONCLUSION: Lower lung volumes are associated with increased vascular stiffness at an early age. The interaction between lung function and vascular stiffness may thus represent more than just age-related alterations in both the pulmonary and vascular systems.